2010
DOI: 10.1111/j.1095-8649.2010.02804.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological correlates of seasonal growth patterns in lake trout Salvelinus namaycush

Abstract: Physiological correlates of seasonal growth patterns were measured in lake trout Salvelinus namaycush from two populations with contrasting diets (zooplankton-dominated diet in Louisa Lake; fish-dominated diet in Opeongo Lake). Fish in Opeongo Lake grew faster and were in better condition than fish in Louisa Lake. The most prominent biochemical difference between populations was higher citrate synthase (CS) and cytochrome c oxidase activity in the white muscle of fish from Opeongo Lake, indicating greater sust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…First, increased reliance on Mysis and zooplankton would be less energetically efficient than foraging on larger prey fish or benthic invertebrates because predatory fish are more active when forced to feed on numerous, smaller prey (22). This increased energetic cost of feeding on small prey has been illustrated by studies that found predatory fish in lakes without pelagic prey fish had increased muscle activity and greater activity rates than those same species in lakes containing pelagic prey fish (23)(24)(25) and by studies showing that more active fish generally grow more slowly (26). Additionally, in oligotrophic lakes, the littoral zone is often more productive and smaller in volume than the pelagic zone (6,17), and therefore the probability of a lake trout's encountering prey would be higher in the littoral zone than in the pelagic zone, increasing foraging success but also reducing the time required to find prey.…”
Section: Discussionmentioning
confidence: 92%
“…First, increased reliance on Mysis and zooplankton would be less energetically efficient than foraging on larger prey fish or benthic invertebrates because predatory fish are more active when forced to feed on numerous, smaller prey (22). This increased energetic cost of feeding on small prey has been illustrated by studies that found predatory fish in lakes without pelagic prey fish had increased muscle activity and greater activity rates than those same species in lakes containing pelagic prey fish (23)(24)(25) and by studies showing that more active fish generally grow more slowly (26). Additionally, in oligotrophic lakes, the littoral zone is often more productive and smaller in volume than the pelagic zone (6,17), and therefore the probability of a lake trout's encountering prey would be higher in the littoral zone than in the pelagic zone, increasing foraging success but also reducing the time required to find prey.…”
Section: Discussionmentioning
confidence: 92%
“…6c). These genes are known to be associated with growth rate, body size, and metabolism (Morbey et al 2010;Palstra et al 2014;Flanagan et al 2017), making them strong candidates for underlying ecotype divergence in Arctic charr. Additionally, 19 differentially expressed genes were shared across four ecotype pairs, which included several haemoglobin subunits ( Supplementary Fig.…”
Section: Variable and Non-parallel Evolutionary Histories Underlie Pamentioning
confidence: 99%
“…For brevity, we do not present other condition metrics such as Le Cren's condition index (K LC ) or residual mass from the regression of logW on logL F (Rennie and Verdon 2008). However, in our system, K F , K LC , and residual mass are highly correlated (Morbey et al 2010). Large year-toyear variation in size-at-age meant it was not useful to generalize growth using standard descriptive models (e.g., von Bertalanffy) or realistic mechanistic models (e.g., generic biphasic growth model; Lester et al 2004, Quince et al 2008a, Quince et al 2008b).…”
Section: Long-term Trends In Size and Conditionmentioning
confidence: 99%